Mobility patterns of satellite travellers based on mobile phone cellular data - Michalkó, Gábor; Prorok, Márton; KondorAttila Csaba; Ilyés, Noémi; Szabó, Tünde (Hungarian Geographical Bulletin, 2023)
For a long time, tourism statistics were the only reliable source of information on tourism mobility. Tourism statistics are inadequate for the analysis of tourist mobility within state borders and across Schengen Borders without using registered accommodations. Big data offers the opportunity to gain a better understanding of tourism movements, for example, same-day tourist flows in metropolitan areas. Here, we introduce the concept of the satellite traveller to more effectively investigate the nature of tourism between the large city and its surroundings. As tourists communicate via cellular devices, the use of mobile phones offers an opportunity for researchers to explore the mobility pattern of tourists. In this article, we discuss the specificities of mobility in Hungary by SIM card users registered in foreign countries. The analysis is based on the Telekom database. We seek to answer the question to what extent the information from the satellite tourists’ mobile phone use can help to understand their movements and to identify frequented places less commonly accounted for in tourism statistics. The most important findings of our investigation are (1) the confirmation of former knowledge about spatial characteristics of same-day tourist flows in the Budapest Metropolitan Region, (2) the insight that far away settlements are also visited by satellite travellers, and (3) the methodological limitations of mobile phone cellular data for tourism mobility analysis.